The Agility Total Ankle Arthroplasty: A Concise Follow-up at a Minimum of 20 Years. (October 2021) - Bedard, Nicholas; Saltzman, Charles L.; Den Hartog, Taylor; Carlson, Samuel; Callaghan, John; Alvine, Greg; Alvine, Frank
Background: Between 1984 and 1994, a single surgeon performed 132 primary cementless total ankle replacements using the Agility total arthroplasty system. The purpose of this study was to report on the 20-year follow-up, which we believe is the first study with this length of follow-up. Methods: Living patients were contacted and interviewed to determine the status of their implant (revised or unrevised) and to answer a simple questionnaire concerning overall satisfaction, pain, and functional improvement, as in a previous study. Thirty-three (26.2%) patients with 33 (25%) ankles of the original series were alive at a minimum of 20 years postoperatively, with a median follow-up of 22 years. They were asked to return to the office for standing anteroposterior and lateral ankle and foot radiographs or to send these radiographs if performed elsewhere. Radiographs were evaluated for radiolucencies around the components and subsidence (talar component) or migration (tibial component) of components. Results: Seventeen (13.5%) ankles of the 126 available for follow-up, including 5 (15.2%) ankles in living patients, had undergone revision ( n = 10) or arthrodesis ( n = 7) for loosening. One additional ankle was revised for infection and 1 for talar component malposition; thus, 19 (15.1%) ankles were revised. Conclusion: These results should provide a 20-year benchmark for newer total ankle arthroplasty designs when a similar length of follow-up becomes available. Level of Evidence: Level III, retrospective cohort study.